Comparative Performance Analysis of GPU and CPU Processing for Digital Filtering Operations on Images Captured by the NAO Humanoid Robot - Souza, Vitor Amadeu (Anais do Workshop em Desempenho de Sistemas Computacionais e de Comunicação (WPerformance), 2026)
This work presents a quantitative comparison of GPU and CPU performance for digital image filtering operations, using the NAO humanoid robot as the image source. Three algorithms were evaluated: Gaussian filtering, Sobel filtering, and FFT-based high-pass filtering, with experiments varying batch size (1 to 50 images) and resolution (320×240 to 1280×960 pixels). Results show that GPU advantage is operation-dependent: FFT achieved speedups of up to 63.26× at high resolution, while Gaussian filtering only outperformed CPU for larger batch sizes. Operation-specific efficiency thresholds were established, providing practical guidelines for architecture selection in robotic computer vision systems.